Ethical and Sacred Respect for Nature. Rolston's Ecological Ethics in Science, Philosophy and Theology - Armengol , Guillermo (Pensamiento. Revista de Investigación e Información Filosófica, 2008)
Holmes Rolston III is an American philosopher who trained as a physicist and mathematician and who has spent his academic life in the philosophy department of Colorado State University. The son of a Presbyterian minister, he himself is also a pastor in the Presbyterian Church, despite deciding to dedicate his life to academia. Although retired, he still remains intellectually active. Among the many prizes and accolades he has won throughout his career, the Templeton Prize in 2003 was the one which, without doubt, most served to popularise his name and work.